2019
DOI: 10.1186/s13601-019-0252-0
|View full text |Cite|
|
Sign up to set email alerts
|

Guidance to 2018 good practice: ARIA digitally-enabled, integrated, person-centred care for rhinitis and asthma

Abstract: AimsMobile Airways Sentinel NetworK (MASK) belongs to the Fondation Partenariale MACVIA-LR of Montpellier, France and aims to provide an active and healthy life to rhinitis sufferers and to those with asthma multimorbidity across the life cycle, whatever their gender or socio-economic status, in order to reduce health and social inequities incurred by the disease and to improve the digital transformation of health and care. The ultimate goal is to change the management strategy in chronic diseases.MethodsMASK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
95
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(103 citation statements)
references
References 94 publications
0
95
0
8
Order By: Relevance
“…Consider referral to a specialist and allergen immunotherapy and Management of Non-Communicable Diseases'' as a good practice that can be scaled up in the field of digitally enabled, integrated, person-centered care. 56 Messages from MASK. Two studies in more than 9000 users and 22 countries 24,57 confirmed a pilot study 23 and allowed differentiation between allergic rhinitis treatments.…”
Section: Rwe Using Mobile Technologymentioning
confidence: 99%
“…Consider referral to a specialist and allergen immunotherapy and Management of Non-Communicable Diseases'' as a good practice that can be scaled up in the field of digitally enabled, integrated, person-centered care. 56 Messages from MASK. Two studies in more than 9000 users and 22 countries 24,57 confirmed a pilot study 23 and allowed differentiation between allergic rhinitis treatments.…”
Section: Rwe Using Mobile Technologymentioning
confidence: 99%
“…ICPs have been proposed with a focus on mHealth technologies that should enhance self‐management and adherence to guidelines and ICPs. An innovative patient‐centered approach for ICPs has been proposed by the ARIA expert group for rhinitis and asthma multi‐morbidity …”
Section: Next‐generation Care Pathways Of Cat Allergymentioning
confidence: 99%
“…MASK (Mobile Airways Sentinel network) uses mobile technology to develop care pathways for the management of rhinitis and asthma by a multidisciplinary group and by patients themselves . The scaling up strategy uses the recommendations of the European Innovation Partnership on Active and Healthy Ageing …”
Section: Discussionmentioning
confidence: 99%